2008
DOI: 10.1176/appi.ap.32.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Peer Group Mentoring of Junior Faculty

Abstract: A peer group mentoring format for junior faculty in an academic department of psychiatry can be an effective model of mentoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 14 publications
0
77
0
Order By: Relevance
“…The literature has identified informal mentoring models such as: peer mentoring in which people of similar rank who share interests work together toward common goals (Bussey-Jones et al 2006;Seritan et al 2007;Files et al 2008;Mayer et al 2008;Moss et al 2008;Santucci et al 2008); multiplementoring in which the mentee is encouraged to develop a mentoring community consisting of a few mentors who seek to address and support the various aspects and the needs of the mentee (Chesler & Chesler 2002); and a two-tiered program involving 1 year perceptoring and multi-year mentoring (Benson et al 2002).…”
Section: Mentorshipmentioning
confidence: 99%
“…The literature has identified informal mentoring models such as: peer mentoring in which people of similar rank who share interests work together toward common goals (Bussey-Jones et al 2006;Seritan et al 2007;Files et al 2008;Mayer et al 2008;Moss et al 2008;Santucci et al 2008); multiplementoring in which the mentee is encouraged to develop a mentoring community consisting of a few mentors who seek to address and support the various aspects and the needs of the mentee (Chesler & Chesler 2002); and a two-tiered program involving 1 year perceptoring and multi-year mentoring (Benson et al 2002).…”
Section: Mentorshipmentioning
confidence: 99%
“…As a result, some ECPs may begin their careers feeling isolated and perhaps experiencing benign neglect (i.e. inadvertent inattention without malicious intent) and mismatched expectations of mentoring relationships with senior colleagues (Moss, Teshima, & Leszcz, 2008). Henderson-Daniel speaks to the professional isolation faced by African American women psychologists in academia while others describe the impact of benign neglect on individuals of diverse backgrounds and professional disciplines (Austin, Sorcinelli, & McDaniels, 2007; Committee for the Assessment of NIH Minority Research Training Programs, Oversight Committee for the Assessment of NIH Minority Research Training Programs, Board on Higher Education and Workforce, & National Research Council, 2005;Pololi, Cooper, & Carr, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring has been shown to be effective in preparing junior faculty for their new roles. [4,13,[18][19][20][21][22] Several specific benefits from mentoring have been identified and proposed by research. Kapustin and Murphy's [18] review of the literature reported that mentoring was associated with high productivity and retention.…”
Section: The Role Of Mentoring In Faculty Developmentmentioning
confidence: 99%
“…Peer mentoring can be an effective and an inexpensive alternative to the traditional dyadic mentoring model [21]. Junior faculty participants in a year-long peer mentoring program reported satisfaction and were interested in continuing participation the following year [21].…”
Section: The Role Of Mentoring In Faculty Developmentmentioning
confidence: 99%
See 1 more Smart Citation